2019
DOI: 10.1097/aln.0000000000002711
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Partial Neuromuscular Block and the Ventilatory Response to Hypoxia

Abstract: Editor’s Perspective What We Already Know about This Topic What This Article Tells Us That Is New Background The ventilatory response to hypoxia is a life-saving chemoreflex originating at the carotid bodies that is impaired by nondepolarizing neuromuscular blocking agents. This study evaluated the effect of three strategies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…By showing that the response to hypercapnia was not significantly affected, it was hypothesized that muscle relaxants exerted these effects within the peripheral chemoreflex loop at the peripheral chemoreceptors. Similar observations have been made recently for the more commonly used muscle relaxant rocuronium [9]. Together, these studies show that a shallow neuromuscular block (e.g., train-of-four muscle twitch response ratio of 70 to 90%, see ref [26].…”
Section: Anesthetic Drug Effects On Peripheral Chemosensitivitysupporting
confidence: 83%
See 3 more Smart Citations
“…By showing that the response to hypercapnia was not significantly affected, it was hypothesized that muscle relaxants exerted these effects within the peripheral chemoreflex loop at the peripheral chemoreceptors. Similar observations have been made recently for the more commonly used muscle relaxant rocuronium [9]. Together, these studies show that a shallow neuromuscular block (e.g., train-of-four muscle twitch response ratio of 70 to 90%, see ref [26].…”
Section: Anesthetic Drug Effects On Peripheral Chemosensitivitysupporting
confidence: 83%
“…However, as cholinergic transmission is primarily involved in modulatory effects in the chemoreflex loop, the exact effect of muscle relaxants on the type 1 cell and chemotransduction process is not known. One example that supports the hypothesis that muscle relaxants interfere with cholinergic chemotransmission is that, following administration of rocuronium, the AHVR is depressed, an effect that is just partly related to the reduction in muscle strength [9].…”
Section: Anesthetic Drug Effects On Peripheral Chemosensitivitymentioning
confidence: 83%
See 2 more Smart Citations
“…Additional data are available to support return of the TOF ratio to unity. Broens and colleagues 14 recently reported that 'Despite full reversal of partial neuromuscular block at the thumb, impairment of the peripheral chemoreflex may persist at train-of-four ratios greater than 0.9 following reversal with neostigmine and sugammadex [sic] or spontaneous recovery of the neuromuscular block.' This study was performed in healthy volunteers (with no premedication or sedation), and neuromuscular monitoring included electromyography, a technique that is devoid of the inverse fade phenomenon (TOF ratios >1.0 that require normalisation) that plagues acceleromyography.…”
mentioning
confidence: 99%